CRITICAL ANALYSIS OF ISLAMIC PHILOSOPHY ON SOCIAL MEDIA: A STUDY OF FAHRUDDIN FAIZ’S YOUTUBE CONTENT - Humaidi, Humaidi; Sairi, Muhammad; Husaeni, Fahri (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2025)
YouTube is one of the most visited platforms globally. Its position is second only to Google and has a major role in the dissemination of information on Islamic philosophy. One notable YouTube channel serving as a resource is Fahruddin Faiz at the Ngaji Philosophy channel. This endeavor takes place weekly on Wednesday evenings at the General Sudirman Mosque, Yogyakarta. The recorded sessions are subsequently shared on the MJS and Media Kontji YouTube channels. The focus of this study is on episode 37 on the MJS YouTube or 38 on the Media Koentji, which delves into the Ngaji Philosophy: Pre-Discourse-Islamic Philosophy. The research findings suggest that the YouTube channel of Ngaji Philosophy has significantly impacted the understanding of Islamic philosophy among students in Indonesian Islamic Universities. These results stem from a survey involving 114 students across five Islamic Theology and Philosophy (ITP) study programs in Indonesia. However, there is an inconsistency in defining Islamic philosophy and historical facts. The implication is the blurring of the meaning of Islamic philosophy, which has an impact on the scope and study. The definition used is not by the standards for making definitions, and the definitions conveyed by muslim philosophers. While historically, Faiz’s statement is contradictory and incoherent with the historical works of Islamic philosophy. The approach used in this study is critical analysis and cross-reference techniques. This method functions, first, as complementary data for the explanation and, second, as validation and evidence that Faiz’s definition and explanation are incoherent.